Effect of Syngas Composition on the Combustion and Emissions Characteristics of a Syngas/Diesel RCCI Engine - Navid Kousheshi; Mortaza Yari; Amin Paykani; Ali Saberi Mehr; German F. de la Fuente (Energies, 2020)
Reactivity controlled compression ignition (RCCI) strategy uses two different fuels with different reactivities which provides more control over the combustion process and has the potential to dramatically lower combustion temperature and NOX and PM emissions. The objective of the present study is to numerically investigate the impact of syngas composition on the combustion and emissions characteristics of an RCCI engine operating with syngas/diesel at constant energy per cycle. For this purpose, different syngas compositions produced through gasification process have been chosen for comparison with the simulated syngas (mixture of hydrogen and carbon monoxide). The results obtained indicate that using syngas results in more soot, CO and UHC emissions compared with simulated syngas. Even though more NOX reduction can be achieved while operating with syngas, the engine could suffer from poor combustion and misfire at low loads due to the presence of nitrogen in the mixture. In terms of exergy, both syngas mixtures lead to more exergy destruction by the increase of syngas substitution. Nevertheless, the magnitude of exergy destruction for simulated syngas is less than the normal syngas.